DOI: 10.26686/wgtn.16997929
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Management of Small Farm Dams in Hawke's Bay, New Zealand

Abstract: <p>In New Zealand, thousands of small dams have been built in agricultural areas for the purpose of providing water storage for stock and/or irrigation. These dams interrupt flow on perennial or intermittent streams; however, almost nothing is known of the downstream impact of these dams on flow regime, water quality, sediment transfer, and channel morphology. The cumulative impact of these dams at the catchment scale is likely to be significant. The present research was undertaken in the Ruataniwha Plai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 128 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Habets et al [18] point out that during dry years, the reduction in annual discharge tends to be twice as high as in median years, and these results can be observed even without changes in the small reservoir network, just due to the seasonality of the climate. For dry years, the reported decreases in the annual discharges have a high range, from values close to 0% to values up to 50% [1,12,45,46]. The results for dry years in our simulations suggest the an increase in the number of small reservoirs leads to an intensification of the hydrological drought during the dry years, since these years have a higher percentage of flow reduction with the increase in the number of small reservoirs.…”
Section: Annual Streamflow Anomalymentioning
confidence: 48%
“…Habets et al [18] point out that during dry years, the reduction in annual discharge tends to be twice as high as in median years, and these results can be observed even without changes in the small reservoir network, just due to the seasonality of the climate. For dry years, the reported decreases in the annual discharges have a high range, from values close to 0% to values up to 50% [1,12,45,46]. The results for dry years in our simulations suggest the an increase in the number of small reservoirs leads to an intensification of the hydrological drought during the dry years, since these years have a higher percentage of flow reduction with the increase in the number of small reservoirs.…”
Section: Annual Streamflow Anomalymentioning
confidence: 48%
“…Stecher and Herrnegger (2022) reported that the impact of reservoir is related with the ratios of the reservoir catchment and the total catchment area, and the ratios of storage capacity and the catchment area. Despite reservoir related metrics used in this study not acting as a good predictor of event characteristics, the paired catchment analysis demonstrates that the alterations of ERC and Np are associated with the reservoir flow regulation in some catchments (Figure 8), highlighting that the effect of reservoirs should not be neglected (Ficklin et al., 2018; Singh & Basu, 2022; Thompson, 2012; Xu et al., 2022).…”
Section: Discussionmentioning
confidence: 86%
“…To analyze specific anomalies in our results in more detail, the concept of paired‐catchment approach (Folton et al., 2015; Gebremicael et al., 2020; Prosdocimi et al., 2015; Singh & Basu, 2022; Thompson, 2012; Van Loon et al., 2019) is employed. In this analysis, we focus on comparing the differences with and without the anomalous behaviors in the paired catchments rather than changes over time.…”
Section: Methodsmentioning
confidence: 99%